2015
DOI: 10.1186/s40163-015-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

Using basic neurobiological measures in criminological research

Abstract: Research on the relationship between neurobiological factors and antisocial behavior has grown exponentially in recent decades. As a result, criminal behavior has been related to impairments in different biological systems, such as genetics, hormones and brain functioning. The development of innovative techniques, for example brain imaging techniques and physiological measurements, can partially explain the increase in neurobiological studies on criminal behavior. Despite a recent zeitgeist change, which has l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 123 publications
(157 reference statements)
0
9
0
Order By: Relevance
“…Future treatment evaluations should continue to integrate biopsychological measures into their design to examine whether these factors act as mechanisms or moderators in treatment effectiveness. While this task may appear daunting, Cornet (2015b) provides practical and cost-efficient recommendations for how researchers can integrate biopsychological measures into their evaluations. It is our hope that incorporating these types of data into treatment evaluations can help to further improve the effectiveness of EBPs across the life course.…”
Section: Discussionmentioning
confidence: 99%
“…Future treatment evaluations should continue to integrate biopsychological measures into their design to examine whether these factors act as mechanisms or moderators in treatment effectiveness. While this task may appear daunting, Cornet (2015b) provides practical and cost-efficient recommendations for how researchers can integrate biopsychological measures into their evaluations. It is our hope that incorporating these types of data into treatment evaluations can help to further improve the effectiveness of EBPs across the life course.…”
Section: Discussionmentioning
confidence: 99%
“…Several indirect measures of neurological health and functioning are readily available (e.g., Wechsler Intelligence Scales, Peabody Picture Vocabulary Test–Revised, California Achievement Test, and Cambridge Neuropsychological Test Automated Batteries; Cornet, 2015), and have repeatedly been shown to predict serious and persistent criminal behavior (Moffitt, 2006; Moffitt, Lynam, & Silva, 1994; Ogilvie, Stewart, Chan, & Shum, 2011). It has previously been suggested that information obtained from these assessments could be used by practitioners in the criminal justice system to guide decision making (Hendrix, Doebbeling, & Aalsma, 2012; Hoge, 1999).…”
Section: Integrating Biosocial Criminology and The Risk-need-responsimentioning
confidence: 99%
“…Based on the available evidence and the ease with which practitioners can assess them in correctional settings, measures of neurological risk factors may be among the most promising items to consider in attempting to improve risk prediction. Neurological functioning can be evaluated using indirect measures such as formalized tests designed to assess intelligence, verbal skills, and executive functions (Cornet, 2015; Fishbein & Sheppard, 2006; Hendrix et al, 2012; Hoge, 1999). For example, the Go/No-Go task is commonly used to examine one’s ability to inhibit responses to various stimuli.…”
Section: Integrating Biosocial Criminology and The Risk-need-responsimentioning
confidence: 99%
See 2 more Smart Citations